Effectiveness of Problem-Based Learning Module as An Instructional Tool in Improving Scientific Argumentation Skill - Sindy Nurinda; Sajidan Sajidan; Baskoro Adi Prayitno (Biosaintifika: Journal of Biology & Biology Education, 2018)
Scientific argumentation skill required to be mastered in this era. Unfortunately many students still have strunggle improving their scientific argumentation skills. This study was aimed at describing the effectiveness of ecosystem module grounded in Problem-Based Learning in improving scientific argumentation skills. This research was part of the field testing of RD, a research and development previously conducted. Research participants included tenth grade senior high school students. Two classes were selected as a control and experiment class. The control class (existing) did not use the module but the experiment class use the module (module class) grounded in Problem Based Learning implemented. Data were collected from written tests and observations. Data analysis used the scoring rubric of scientific argumentation skill aspect which their results were tested with Gain test and independent T-test. The findings showed an increase in scores of the four aspects of scientific argumentation skills from the module class. The highest percentage of aspect was rebuttal aspect (27.27%) followed by evidence 26,06% and reasoning 23.94%, while the aspect of claim increased by 20.61%. The independent t-test results showed that there was a significant difference between pre-test and post-test results of the module class. It can be concluded that the ecosystem module with problem-based learning material was effective to improve students’ scientific argumentation skills. The product of this reasearch can be use as a tools to improve students’ scientific argumentation skills.